Clinical Outcomes and Midterm Mortality After Carotid Endarterectomy: A Single Center Study - Muhammed Bayram; Emre Yasar (Genel Tıp Dergisi)
Background/Aims: This single-center study aimed to investigate the clinical outcomes and midterm mortality in patients who underwent carotid endarterectomy (CEA) for various indications. Methods: The study included 109 patients who underwent CEA at our institution. Demographic characteristics, indications for surgery, operative techniques, and early postoperative complications were recorded. Follow-up data were obtained for a mean period of 23.3 ± 17.2 months, and mortality causes, and neurological outcomes were analysed. Results: The mean age of the patients was 66.53 ± 8.00 years, with 73 men and 36 women. Indications for CEA included transient ischemic attack (TIA) in 21.1% and a history of ischemic stroke in 26.6% of patients. Overall, 86.2% had ipsilateral carotid stenosis of 70% or more. Most patients (89.9%) were operated under general anesthesia, and the conventional carotid endarterectomy technique was most employed (78.0%). The most frequent reconstruction method for the longitudinal carotid arteriotomy was Dacron patch plasty (56.0%). Early follow-up revealed low hospital mortality (0.9%) and limited postoperative complications (3.7% TIA, 1.8% major neurological complications, and 1.8% minor neurological complications). During the follow-up period, absolute survival was 87.0%. Conclusions: Our study demonstrates favourable early outcomes and acceptable long-term mortality rates following CEA. However, larger, and multicentre studies are warranted to further validate these results and enhance our understanding of CEA's long-term benefits